2009
DOI: 10.1007/s11663-009-9294-3
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of the Simultaneous Carbothermic Reduction of FeO and MnO from High-Carbon Ferromanganese Slag

Abstract: The carbothermic reduction of 38.7 pct MnO-12.1 pct pct MgO-9.3 pct Al 2 O 3 -24.1 pct SiO 2 -10.4 pct FeO slag in Ar at 1600°C was studied using the sessile drop wettability technique. Pure graphite, coke, and charcoal were used as the carbon material substrates. The reduction rates were evaluated by sampling at different reduction times and by analyzing the chemical compositions of the reduced slag and the produced metal. The carbothermic FeO reduction from slag is initially fast followed by a much slower r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 9 publications
1
30
0
Order By: Relevance
“…The increase in porosity has the chance to impact on wettability with increased surface roughness, inducing improved wetting and thus improving reaction rates and extents. This noted, similar work by Safarian et al 17) found that more than the surface roughness or CO2 reactivity of a carbonaceous substrate, the 'type' of carbon had a larger effect, suggesting that the porosity increase may only partially impact on wetting and/or reduction of high MnO containing slags.…”
Section: % H) Figs 3(a)-3(c) Illustratessupporting
confidence: 68%
See 2 more Smart Citations
“…The increase in porosity has the chance to impact on wettability with increased surface roughness, inducing improved wetting and thus improving reaction rates and extents. This noted, similar work by Safarian et al 17) found that more than the surface roughness or CO2 reactivity of a carbonaceous substrate, the 'type' of carbon had a larger effect, suggesting that the porosity increase may only partially impact on wetting and/or reduction of high MnO containing slags.…”
Section: % H) Figs 3(a)-3(c) Illustratessupporting
confidence: 68%
“…[16][17][18][19] The study involved the use of a laboratory scale horizontal alumina tube furnace (schematics shown in Fig. 2).…”
Section: Carbon/slag Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…If there is FeO in the slag, this is reduced initially and then a FeMn alloy is produced through further MnO reduction. 4 If the initial slag does not contain FeO, the produced Mn through the carbothermic reduction is rapidly evaporated due to the high vapor pressure of Mn at elevated temperatures as described in our previous work 1) .…”
Section: Introductionmentioning
confidence: 97%
“…FeO and even Fe can be also formed in solid state; however, we here assume that Fe is mainly produced from FeO in the slag. Reactions [6] through [10] show the reduction mechanism of FeO and SiO 2 at slag/gas, gas/metal, and slag/metal interfaces as observed by Pomfret and Grieveson, [26] Teasdale and Hayes, [27] and Safarian et al [28] A simple illustration can be given as in Table VII. WDS Analysis of Phases Observed in B-, G-, and I-Slag Structures Shown in Fig.…”
Section: B Smelting-reduction Thermochemistrymentioning
confidence: 93%